Alumni Views and The Potential of Social Impact on Career Counselling Guidance Policy at The University Level - Wienda Gusta; Zakirman Zakirman; Neviyarni Suhaili (Universitas Pahlawan Tuanku Tambusai, 2021)
Work is related to one's life and social level in society. The current high unemployment rate can be caused by the lack of preparedness of graduates of education institutions, especially university graduates facing the world of work. To overcome this problem several universities have implemented career counseling guidance services. This study aims to see how far the benefits felt by alumni and the potential social impact caused by the implementation of career counseling guidance services at the University level. This type of research is descriptive qualitative, with samples taken are some graduates from two leading universities in West Sumatra, namely IAIN Batusangkar and UIN IB Padang. Data in the study were collected using a questionnaire distributed randomly to 42 respondents online. After filling out the questionnaire online, it can be done by analyzing the data related to the social impact felt by the alumni after the implementation of career counseling activities by the university. Based on the data analysis that has been carried out, it can be concluded that career counseling guidance activities according to the alumni proved to be very effective in assisting in obtaining jobs. Indirectly with the existence of career counseling guidance services can reduce the unemployment rate so that it will have a significant impact socially in the community environment.